1999
DOI: 10.1016/s0893-133x(99)00011-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered Activity of Midbrain Dopamine Neurons Following 7-Day Withdrawal from Chronic Cocaine Abuse is Normalized by D2 Receptor Stimulation During the Early Withdrawal Phase

Abstract: Using in vivo single-unit recording in rats, we compared the effects of continuous cocaine infusion via minipump or single daily injections (both 40 mg/kg/d ϫ 14 days, SC) on the activity of putative dopamine (DA) neurons in the substantia nigra pars compacta (SNC) and ventral tegmental area (VTA).The two opposite behavioral outcomes in animal models of chronic cocaine or amphetamine abuse are sensitization and tolerance, which are induced by intermittent injection or continuous infusion, respectively (Inada e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Autoreceptor sensitivity has been shown to be altered following chronic exposure to stimulants (Lee et al 1999; Mateo et al 2005; Calipari et al 2014). Here we wanted to assess autoreceptor function in both the NAc core and shell regions following chronic ethanol exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Autoreceptor sensitivity has been shown to be altered following chronic exposure to stimulants (Lee et al 1999; Mateo et al 2005; Calipari et al 2014). Here we wanted to assess autoreceptor function in both the NAc core and shell regions following chronic ethanol exposure.…”
Section: Resultsmentioning
confidence: 99%
“…DA neurons population activity is increased (Lee et al 1999;Gao et al 1998). This effect is reversed by blockade and desensitization of D2R, suggesting changes in the function of D2R involved in feedback inhibition in the VTA-NAc pathway (Lee et al 1999;Gao et al 1998).…”
Section: Effects Of Chronic Administration Of Drugs On the Neuronal Amentioning
confidence: 98%
“…Decreases in extracellular dopamine levels in the nucleus accumbens have also been reported following cocaine withdrawal (Parsons et al, 1991; Robertson et al, 1991; Rossetti et al, 1992; Weiss et al, 1992). Cocaine administration has also been shown to alter the sensitivity of D2 autoreceptors of the midbrain (Gao et al, 1998; Lee et al, 1999; Marinelli et al, 2003), which could reduce pre-synaptic dopamine release. In addition to these functional changes in dopamine signaling, animal studies have also shown that cocaine exposure produces morphological changes in dopamine neurons.…”
Section: Significance Of the Hypodopaminergic State In Cocaine Abusementioning
confidence: 99%